Profile of Strengthening Character Education in Biology Learning of First Grade (10Th Class) Senior High School in MAN 1 Medan - Tara Wardana; Rohani Rohani (Universitas Labuhanbatu, 2024)
Strengthening Character Education (PPK) is an educational movement in schools to strengthen students' character through harmonization of heart (ethics), feeling (aesthetic), thought (literacy), and sports (kinesthetic) with the support of public involvement and cooperation between schools, family, and society. This research aims to determine the profile of strengthening character education in class X biology learning at MAN 1 Medan. The method used in this research is a qualitative method with a descriptive research type using observation, interview and documentation guide sheets in collecting data. Meanwhile, data analysis techniques involve data reduction, data presentation and conclusions. This research was carried out at MAN 1 Medan. Research submitted to describe and analyze events, phenomena, learning activities, attitudes and perceptions. The results of this research show: (1) There are 10 profiles of strengthening character education at MAN 1 Medan, namely: Civilized (ta'addub), Exemplary (qudwah), Citizenship and nationality (muwaṭanah), Taking the middle path (tawassuṭ), Balanced (tawāzun ), Straight and firm (i'tidāl), Equality (musāwah), Deliberation (syūra), Tolerance (tasāmuh), Dynamic and innovative (tathawwur wa ibtikâr). (2) The application of character education in biology learning in class social care, and environmental care. (3) Difficulty implementing character education in biology learning. Teachers do not experience difficulties because biology learning is identical to everyday life in the learning process so it is easy to instill character values in students